Phytobiotic effect of mixed powder of medicinal plants on productivity and egg quality of laying hens - R. Rodríguez (Cuban Journal of Agricultural Science, 2023)
To evaluate the phytobiotic effect of the mixed powder of medicinal plants on the productivity and egg quality of laying hens, 120 White Leghorn birds (Hybrid L-33), 27 weeks old, were used. For 10 weeks, the animals were placed according to a completely randomized design with three treatments, 10 repetitions per treatment and four birds per repetition. The experimental treatments consisted of a basal diet (T1) and the addition of 0.5 (T2) and 1.0 % (T3) of the mixed powder of leaves of medicinal plants (40 % of Anacardium occidentale, 20 % of Psidium guajava, 20 % of Moringa oleifera and 20 % of Morinda citrifolia). T3 improved (P<0.05) laying intensity (80.18 to 85.53 %) and mass conversion (2.73 to 2.52) and reduced (P<0.05) the percentage of cracked eggs (0.22 to 0.08 %) in relation to the other experimental groups. However, diets did not change (P>0.05) the body weight of hens, egg weight, feed intake and broken, shell-less and dirty eggs, as well as external (shape index, weight, thickness, and surface area of the shell) and internal (albumen and yolk height, Haugh units and yolk color) quality of the egg of laying hens. Dietary addition of 1.0 % of mixed powder of medicinal plants (40 % A. occidentale, 20 % P. guajava, 20 % M. oleifera and 20 % M. citrifolia) is recommended to improve productive efficiency and reduce cracked eggs from laying hens.